High efficient rubber toughened polyester composite towards next generation / Noor Najmi Bonnia, Aein Afina Redzuan and Nurul Shakirah Shuhaimeen - Bonnia, Noor Najmi; Redzuan, Aein Afina; Shuhaimeen, Nurul Shakirah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Brittleness of thermoset polyester due to crosslinking process enhances the idea of producing rubber toughened polyester composite. Rubber toughened polyester-kenaf composite were prepared by adding various percentage of filler (synthetic / natural) in unsaturated polyester resin and subsequently cross-linked using methyl ethyl ketone peroxide and accelerator cobalt Octanoate. Liquid Natural Rubber (LNR) was added and act as toughening agent in this composite. Product is expected to be applied in the interior of passenger cars and truck cabins. This is a quality local product from a combination of good properties polyester and high performance natural fiber/ synthetic filler, kenaf and carbon black that is suitable for many applications such as in automotive, semiconductor and construction sector. Addition of LNR promotes excellent properties on impact, flexural and hardness compare to without LNR. Addition of higher percentage of kenaf will lead the composite to elastic behavior and decrease the toughened properties of the composite. The advantages of rubber toughened polyester have widened the applications of polyester resin within the area of automotive, transport, aircraft and sporting